Attitudes towards research in obstetricians in training at a private university, Metropolitan Lima - 2022 - Vega-Gonzales, Emilio (2023)
Introduction: The research addresses one of the components of the professional profile that receives less attention from university students, which is reflected in a low number of annual scientific publications. Knowing the attitude of students towards research can be very useful for proposing proposals for improvement and taking advantage of the research potential that many obstetricians in training have.Objective: To determine the attitudes towards research in obstetricians in training at a private university in Metropolitan Lima.Materials and Methods: Observational, descriptive cross-sectional design. The study was carried out through a virtual survey provided to obstetricians in training at a private university in Metropolitan Lima, obtaining a final sample of 51 students. The study variable is the attitude towards research, and age and academic year were used as control variables. The collection technique was the survey, and the instrument used was the Arellano Research Attitudes Assessment Scale. The results were presented by means of relative frequencies and score averages, and for the association with the control variables, the chi square was used with 5% significance.Results: A regular attitude towards research was found in 45.1%, followed by a bad attitude in 43.1%. The attitudes towards the elaboration of articles and participation in research presented better averages with 3.86 and 3.77 respectively; while the attitudes towards the parameters of the university and the possibility of doing research for it had the lowest averages with only 2.52 and 2.64, respectively. No significant association was found with age or academic year (p>0.05).Conclusions: The attitude towards research of obstetricians in training is regular to low, but shows an interest in writing articles and participating in activities in this training area.